Circulating Sezary cells in subacute spongiotic dermatitis - Srivastava, Srijan; Mishra, Jyoti; Kaushik, Rajni; Gulati, Archana (Indian Journal of Case Reports, 2020)
Sezary syndrome comprises a triad of fiery red erythroderma, generalized lymphadenopathy, and circulating atypical cells with cerebriform nuclei (Sezary cells) exceeding an absolute value of 1000/cumm or exceeding 10% of circulating cells. Sezary cell is not pathognomonic of Sezary syndrome and can be seen in many benign dermatoses such as chronic eczema, psoriasis, lupus erythematosus, parapsoriasis, atopic dermatitis, and vasculitis. We report circulating Sezary cells in a patient of subacute spongiotic dermatitis, one of the rare causes for Sezary cells in peripheral blood.